2018
DOI: 10.1093/ejcts/ezy157
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and early outcomes for Type A aortic dissection with preoperative renal dysfunction stratified by estimated glomerular filtration rate

Abstract: Total arch replacement can be safely performed in patients with AAD and preoperative mild renal dysfunction. Preoperative renal dysfunction is a risk factor for postoperative RRT, and eGFR is useful for predicting the requirement for postoperative RRT. Our surgical strategy for total arch replacement and stented elephant trunk for patients with AAD and mild preoperative renal dysfunction has excellent early outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…To compare ND and no ND groups, Cox regression analysis was conducted, and adjusted hazard ratio (HR) and P value were reported. Apart from stroke, covariates entered in this model were age, gender, peripheral arterial disease, ejection fraction under 30%, chronic lung disease, renal function, preoperative critical state, ATAD and high extracorporeal circulation (ECC) time, as these factors are known to be associated with increased postoperative mortality after aortic surgery (2,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…To compare ND and no ND groups, Cox regression analysis was conducted, and adjusted hazard ratio (HR) and P value were reported. Apart from stroke, covariates entered in this model were age, gender, peripheral arterial disease, ejection fraction under 30%, chronic lung disease, renal function, preoperative critical state, ATAD and high extracorporeal circulation (ECC) time, as these factors are known to be associated with increased postoperative mortality after aortic surgery (2,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the aforementioned study also points out some postoperative complications like deep sternal wound infection, pneumonia, and tracheostomy in old age patients which are not emphasized in this study. Similarly, a study by Zhou et al 3 demonstrates that renal replacement therapy and prolonged ventilation requiring tracheotomy were prevalent complications in patients who underwent TAR with preoperative renal dysfunction.…”
mentioning
confidence: 90%
“…In a study by Kenji Okada et al 2 and demonstrated that patients with lower categories of eGFR had considerably different outcomes than higher ones. Another study conducted in 2018 3 had the same approach. Second, the authors excluded the patients with dialysis-dependent end-stage renal disease without stating the relevant reason.…”
mentioning
confidence: 99%
“…In those 46 patients who develop AKI, 12 (26.1%) of them had AKI before TEVAR, and 34 (73.9%) of them developed AKI after the procedure, including 39 (15.2%) in stage I, 4 (1.6%) in stage II, and 3 (1.2%) in stage III. The mean age of the patients was 52.8 ± 9.8 years, 217 (84.9%) were male, 228 (89%) were young and middle-aged people (age 65 years), 201 (78.8%) had a history of hypertension, and the median time elapsed from symptom onset to hospital admission was 7 days (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Compared to the non-AKI group, patients in the AKI group were more likely to have a higher proportion of the youth, have a higher level of body mass index (BMI), shorter time from onset to admission.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The common risk factors for the occurrence of AKI in TAAD patients and TBAD patients include baseline renal function, blood pressure, renal artery involvement, etc. [3,[10][11][12]. The risk factors of AKI for patients who underwent surgery for TAAD include perioperative sepsis, extracorporeal circulation time, and postoperative 72-h drainage volume, etc.…”
Section: Introductionmentioning
confidence: 99%